Catheter ablation of atrial fibrillation in chronic heart failure: state-of-the-art and future perspectives. Issue 5 (8th February 2016) - Anselmino, Matteo; Matta, Mario; Castagno, Davide; Giustetto, Carla; Gaita, Fiorenzo
Abstract : Catheter ablation of atrial fibrillation (AFCA) is a widely recommended treatment for symptomatic atrial fibrillation (AF) patients refractory to pharmacological treatment. Catheter ablation of AF is becoming a therapeutic option also among patients with chronic heart failure (CHF), on top of optimal medical treatment, being this arrhythmia related to a higher risk of death and/or symptom's worsening. In fact, in this setting, clinical evidences are continuously increasing. The present systematic review pools all published experiences concerning AFCA among CHF patients, or patients with structural cardiomyopathies, in order to summarize procedural safety and efficacy in this specific population. Moreover, the effects of AFCA on functional class and quality of life and the different procedural protocols available are discussed. The present work, therefore, attempts to provide an evidence-based clinical perspective to optimize clinical indication and tailor procedural characteristics and endpoints to patients affected by CHF referred for AFCA.